Inhibition of proliferation, migration, and adhesion of skin fibroblasts by enzymatic poly(gallic acid) grafted with L-Arginine, migration, and adhesion of skin fibroblasts by enzymatic poly(gallic acid) grafted with L-Arginine: Effect of PGAL-grafted-L-Arginine on fibroblast - Ortega-Sánchez, Carmina; Pérez-Díaz, Mario Alberto; Martínez-López, Valentín; Zacaula-Juárez, Noé; González-Torres, Maykel; Leyva-Gómez, Gerardo; Hernandez-Valdepeña, Miguel Angel; Gimeno, Miquel; Sánchez-Sánchez, Roberto (Cellular and Molecular Biology, 2023)
Psoriasis and atopic dermatitis (AD) are characterized by enhanced skin inflammation, which results in hyperproliferation and the recruitment of immune cells into the skin. For that reason, it is needed a chemical capable to reduce cell proliferation and the recruitment of cells. The search for new molecules for therapeutic skin treatment mainly focuses on the antioxidant and anti-inflammatory properties, highlighting the rheological properties of polymeric polypeptides. We studied L-arginine (L-Arg) grafted (-g-) to enzymatic poly(gallic acid) (PGAL). The latter is a multiradical antioxidant with greater properties and thermal stability. The derivative was enzymatically polymerized in an innocuous procedure. The poly(gallic acid)-g-L-Arg molecule (PGAL-g-L-Arg) inhibits bacterial strains which also have been involved in the progression of psoriasis and AD. However, it is important to analyze their biological effect on skin cells. The cell viability was analyzed by calcein/ethidium homodimer assays and crystal violet. The proliferation and cell attachment were determined by a curve of time and quantitation of the optical density of crystal violet. To analyze the cell migration a wound-healing assay was performed. This synthesis demonstrates that it is not cytotoxic at high concentrations (250 μg/mL). We observed a decrease in the proliferation, migration, and adhesion of dermal fibroblasts in vitro but the compound could not avoid the increase of reactive oxygen species in the cell. Based on our findings, PGAL-g-L-Arg is a promising candidate for treating skin diseases such as psoriasis and AD where decreasing the proliferation and cell migration could help to avoid inflammation.